(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the proportion of acute stroke classifications and to analyze associated factors in patients treated at Ca Mau General Hospital in 2024. Subjects and methods: A cross-sectional descriptive study was conducted on 1643 patients with acute stroke admitted to Ca Mau General Hospital from January to December 2024. Data were collected from medical records and interviews with patients or their relatives, and analyzed using STATA software version 18.0. Associations between risk factors and stroke classification were assessed using multivariable logistic regression, with statistical significance defined as p < 0.05. Results: The rate of cerebral infarction was 84.18%, much higher than cerebral hemorrhage (15.82%). Some factors associated with cerebral hemorrhage include: male gender (adjusted OR = 2.02; p = 0.01), hypertension (adjusted OR = 2.18; p = 0.01), impaired consciousness (adjusted OR = 4.59; p = 0.01). Conversely, atrial fibrillation was inversely associated with cerebral hemorrhage (adjusted OR = 0.34; p = 0.001). The mortality rate in the cerebral hemorrhage group was significantly higher (46.92% compared to 7.74%). Conclusion: Cerebral hemorrhage accounted for a lower proportion but was associated with a more severe prognosis and multiple factors, including male sex, advanced age, prolonged hypertension, and impaired consciousness. These findings underscore the need to prioritize blood pressure control and risk screening in high-risk groups.